BlackOut : o negro no cinema de Mato Grosso - Pinto, Maurício Rodrigues (2023)
This research documents and discusses, through the intersectionality bias (González; Hill Collins), the presence of black people in Mato Grosso film production financed with public incentives, between 1992 and 2020, either in front of the cameras and/or behind the scenes in directing and writing. For this, a reflection is carried out on the concept of black cinema based on the discussions of Rosa Maria Berardo, Júlio César dos Santos, Jeferson De and also Orlando Senna, as well as on issues of representation and representativeness, addressing the concepts of stereotype (Hall; Araújo), oppositional gaze (bell hooks) images of control and outsider within (Hill Collins; Bueno). Based on these reflections, a chronology of black cinema in Mato Grosso is proposed. Based on methodological procedures based on documentary and content analysis (Bardin), an intersectional mapping of fiction cinema in Mato Grosso carried out with public funding is presented, from which two films considered to be inscribed in the concept of black cinema constructed in this study, are highlighted and analyzed.